2016
DOI: 10.21548/32-2-1378
|View full text |Cite
|
Sign up to set email alerts
|

Modifications in Chemical, Physical and Mechanical Properties of Nebbiolo (Vitis vinifera L.) Grape Berries Induced by Mixed Virus Infection

Abstract: Modifications in grape quality parameters induced by mixed infection with GFLV and GFkV, GLRaV-1 and GVA, and GLRaV-3 and GVA in three Nebbiolo clones were compared against healthy plants of the same clones in two experimental vineyards in Piemonte, northwest Italy. The aim of the study was to evaluate the effect of virus infection on the mechanical properties of the berry skin and the whole berry as assessed by texture analysis tests, and on the amount and quality of berry skin phenols. Differences were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…For example, GLRaV‐3 induces a strong inhibition of carbohydrate and anthocyanin accumulation in berries (Alabi et al., ; Guidoni et al., ; Vega et al., ). Similarly, mixed infections of GFLV + GFkV and of GLRaV‐1 + GVA lead to a significant reduction in tri‐hydroxylated malvidin‐3‐glucoside forms and in phenol extractability in ‘Nebbiolo’ grapes, with a negative impact on the overall wine quality (Santini et al., ), whereas grapevine red blotch‐associated virus (GRBaV) inhibits ripening, reducing the accumulation of pigments and flavours (Blanco‐Ulate et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, GLRaV‐3 induces a strong inhibition of carbohydrate and anthocyanin accumulation in berries (Alabi et al., ; Guidoni et al., ; Vega et al., ). Similarly, mixed infections of GFLV + GFkV and of GLRaV‐1 + GVA lead to a significant reduction in tri‐hydroxylated malvidin‐3‐glucoside forms and in phenol extractability in ‘Nebbiolo’ grapes, with a negative impact on the overall wine quality (Santini et al., ), whereas grapevine red blotch‐associated virus (GRBaV) inhibits ripening, reducing the accumulation of pigments and flavours (Blanco‐Ulate et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the situation with GLRaV-1, these studies reported highly variable findings, which can be difficult to interpret and confusing at times. For example, several studies reported that GLRaV-3 infection reduced berry weight [89,[94][95][96], while others claimed that infection with GLRaV-3 either had no effects or actually increased berry weight [88,[97][98][99][100][101]. Many factors may be attributable for the discrepancy between these studies, including differences in the cultivars and rootstocks used, the genetic variants of GLRaV-3 involved, co-infection with different viruses, age of the infected vines, climate, and methods of sampling.…”
Section: Effects Of Glravs On Physiology Fruit Quality and Gene Exprmentioning
confidence: 99%
“…No changes in either yield or the contents of soluble solids and phenolic compounds (anthocyanins and catechins) were observed [ 87 ]. In contrast, Santini et al, 2011 reported an increase in berry weight and titratable acidity but a reduction in yield in Nebbiolo vines co-infected with GLRaV-1 and GVA [ 88 ]. On the other hand, Guidoni et al, 2000 reported no change in yield, but documented decreased berry weight and titratable acidity level in vines co-infected with GLRaV-1 and GVA [ 89 ].…”
Section: Effects Of Glravs On Physiology Fruit Quality and Gene Expressionmentioning
confidence: 99%
“…GLRaV-1 and rugose wood viruses shift the relative proportion of phenolics from seeds and skins, but do not appear to affect grape anthocyanin or total phenolic contents (Tomažič et al, 2003). In contrast, the level of the more stable (oxidation-resistant) anthocyanins is reduced in Nebbiolo grapes, in association with joint infection with GFV and GFkV viruses (Santini et al, 2011).…”
Section: Consequences Of Pathogenesis For Fruit Qualitymentioning
confidence: 92%